O estádio do espelho e a constituição do eu na esquizofrenia - Mauricio, Thiago Félix (2016)
The present paper analyses the constitution of the I in schizophrenia according to Lacan´s teachings on the theory of the mirror stage. This research deals with it theoretically supported by findings taken from Lacan and Freud´s teachings concerning schizophrenia and the body itself. Other authors´studies on the theory of the mirror stage for the constitution of the I, were also used. Based on the link between the imaginary and the body, the focus was given on the imaginary for the constitution of the I in schizophrenia. It is crystal clear at some point in Lacan´s teachings the mirror stage theory in the constitution of the I when he points out that the image a child develops through another person constitutes the I. Those who suffer from schizophrenia do not reach the so called “orthopedic totality“, described by Lacan to express the complete constitution of the specular image for babies. Three clinical trials are used to make clear the constitution of the I in schizophrenia. In these cases, the inscription of fantasy of a shattered body prevails, which is clearly seen on separated joints, giving ground to the ideia of fragmentation.